Bearing capacity of strip footings on two-layered clay under combined loading. (September 2015) - Rao, Pingping; Liu, Ying; Cui, Jifei
Abstract: In this paper, a lower bound limit analysis in conjunction with finite elements and second-order cone programming (SOCP) is used to determine the bearing capacity of a rigid strip footing placed on two-layered clay subjected to inclined or eccentric loading. The footing is founded on the free surface of the soil mass with no surcharge applied. Two types of footing–soil interfaces are considered: (1) zero tensile capacity and (2) non-zero tensile capacity. The numerical results are presented in the form of failure envelopes in the loading plane, and the corresponding failure mechanisms are also presented. The size and shape of the failure envelopes are dependent on (1) the undrained shear strength ratio ( cu 1 / cu 2 ), where cu 1 and cu 2 are the undrained shear strength of the top and bottom clay, respectively, and (2) the normalized thickness D / B of the upper clay, where D is the thickness of the top clay layer and B is the width of the footing.